Optimal Sizing of Stationary Energy Storage Systems Participating in Primary Frequency Regulation Markets - Arias, Nataly Banol [UNESP]; Romero, Ruben [UNESP]; Lopez, Juan Camilo; Rider, Marcos J. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Stationary energy storage systems (ESSs) are becoming a prominent option to support the power grid via ancillary services. For instance, transmission system operators (TSOs) can take advantage of the fast control capabilities of stationary ESSs to implement primary frequency regulation. However, capital costs are directly related to the battery energy capacity and the power rate of the charger. Thus, from the perspective of the ESS owner, the higher the ESS capacity is, the more expensive the initial investments result. Based on historical frequencies and given a regulation market, this paper proposes a multi-objective approach to determine the optimal size and objective state of charge of an stationary ESS participating in primary frequency regulation. The proposed optimization method is a flexible enumerative approach that, given a set of market rules and an investment cost function, returns the optimal Pareto front of the problem. The Pareto front is a suitable multiobjective optimization method that shows the trade-off between conflicting objective functions: capital cost and availability/profit. Using the regulation market structure of one of the largest TSOs in USA (PJM interconnection), simulations demonstrate that the proposed approach is a flexible and practical decision-making tool, that investors can exploit when designing their ESS to participate in primary frequency regulation markets.
Keywords: ESS sizing; frequency regulation; multi-objective approach; pareto frontier; stationary energy storage systems